The Influence of The Family Environment on Student Achievement - Firmansyah, Andre Yano; Fajriyanti, Nuri Laili; Amaliya, Rizky; Damayanti, Ila Nur; Hardiansyah, Framz (Journal of Practice Learning and Educational Development, 2026)
This article aims to examine the influence of the family environment on student achievement through a systematic literature review approach. A supportive family environment, in the form of emotional support, attention to education, and active parental involvement, has been shown to have a positive impact on student academic achievement. On the other hand, an unharmonious family environment or parental neglect can potentially reduce student motivation and achievement. Through the analysis of various previous studies, this article identifies factors contributing to student achievement, such as the quality of communication within the family, the role of parents in education, and the child's emotional well-being. The results of the systematic literature review show that a conducive and supportive family environment has a significant influence on improving student achievement in school. This article also provides insights into the importance of collaboration between parents, schools, and the community in creating an environment that supports students' academic development.